المنهج العلمي في العلاقة البينية بين علم النفس الاجتماعي والإحصاء: النموذج الإحصائي متساوي الاحتمال في دراسة التمثلات الاجتماعية أنموذجا - براهمة، نصيرة Brahmah, Nasira; بوالفلفل، إبراهيم Boulfelfel, Ibrahim (مؤسسة كنوز الحكمة للنشر والتوزيع, 2017)
إن استنطاق واقع الممارسة الفعلية لدراسة الظواهر الاجتماعية دراسة تكشف الحقيقية الكامنة ورائها، يعزي الخطاب المعلن عن وجود حدود فاصلة بين العلوم، ذلك أن تفسير ظواهر المجتمع بحقوله المختلفة الاقتصادية و السياسية والاجتماعية...يتأسس علي ذلك التكامل والتداخل بين الأسباب والعوامل التي أدت إلى خلقها في الوجود الاجتماعي، والذي يعتبر فيه الإنسان فاعل اجتماعي متكامل لا يمكن فصل جسده عن تفكيره ونفسيته وعلاقاته الاجتماعية، وبالتالي لا يمكن فصل العلوم التي تشتغل بظواهر جسده الفيزيقي والأخرى التي تشتغل بظواهر نفسيته وعلاقاته الاجتماعية إلا في حدود القاعدة المنهجية القائلة كلما اتسعت فئة التحليل قلت قيمتها التصنيفية. تتناول هذه الورقة العلمية الحديث عن التقاطع المعرفي بين علم الاجتماع وعلم النفس، والذي أوجد تقاطعهما علم نفس اجتماعي ثم علم الإحصاء الذي ارتبط بالعلوم الاجتماعية، ما أدى إلى استحداث فضاء معرفي متخصص وهو الإحصاء الاجتماعي الذي تعددت أساليبه وتقنياته على غرار النموذج الإحصائي متساوي الاحتمال المستخدم في دراسة التمثلات الاجتماعية. وعليه تحاول هذه الدراسة الإجابة على التساؤلات التالية: ما طبيعة العلاقة البينية بين العلوم الاجتماعية وعلم الإحصاء؟ ما طبيعة المنهج العلمي المستخدم في العلاقة البينية بين علم النفس الاجتماعي وعلم الإحصاء؟ ما طبيعة النموذج الإحصائي متساوي الاحتمال في دراسة التمثلات الاجتماعية؟
The questioning of the reality of actual practice in the study of social phenomena uncovers the real interpretations underlying these same phenomena. That reveals the attitude announcing the presence of boundaries between disciplines. This is because the interpretation of social, economical and political phenomena is based on the integration and the overlap between the reasons and factors leading to social existence, in which the human considered as an integrated social actor who cannot separate apart his body from his mind, soul and social relationships .It follows that we cannot separate sciences operating on physical aspect and others dealing with psychological and social phenomena except in respect to the limits of methodological rule stating that whenever the category of analysis expands its taxonomical value decreases. This scientific paper considers the intersection of knowledge between sociology and psychology which led to the establishment of social psychology and statistics as a discipline related to a social science which, in turn, has led to the creation of field of specialized knowledge, known as social statistics. The latter present several patterns an techniques such as (in the example of) statistical model equal probability applied in investigating social representations. Therefore, this paper endeavours answering the following questions: What is the nature of interdisciplinary relationship between social sciences and statistics? What is the nature of the scientific method used in interdisciplinary relationship between social psychology and statistics? What is the nature of the statistical model equal probability in investigating social representations?
Keywords: علم النفس الاجتماعي; الإحصاء; التمثلات الاجتماعية; العلاقة البينية